Evaluación de promotores de crecimiento orgánico y químico en la dieta de pollos broiler en el cantón Balsas provincia El Oro - Aguilar Sánchez, Jefferson Andrés (2014)
The response broilers to the inclusion of AEO (organic essential oils) combined with nutrifibe against an APC (antibiotic growth promoter), the production parameters determined, profitability. We worked with 900 chickens COBB 500 day-old, three treatments with three replications of 100 chicks each were formed; treatments were: T1, are in the balanced supply (+ nutrifibe scolded + promoter); T2 (scolded + nutrifibe); T3: (only promoter: At seven weeks old, the treatment reduced consumption was obtained treating two 5930g in weight gain exists statistical difference P<=0.05 between treatments, the greatest increase in weight was treatment two as 3398g there statistical difference with other treatments P<=0.05 and FCR statistical difference exists, treatment best treatment result was two as 1.74 followed by 1.85 and with one last witness . in most profitable economic returns l treatment was treating two as 25.76%. it is concluded that the use of more Nutrifibe scolded as organic compounds in this study were found to be higher than the combined chemical + organic chemical alone.